Kajian Kualitas Air Permukaan di Kabupaten Bojonegoro Menggunakan Pendekatan IKA-NSF - Icha Ayoe Bilbina; Aussie Amalia (Jurnal Serambi Engineering, 2025)
Surface water in Bojonegoro Regency plays a crucial role in meeting domestic, agricultural and ecosystem needs. However, various human activities, such as excessive use of chemical fertilizers in agricultural areas, have led to a decline in water quality. This study analyses the surface water quality using the National Sanitation Foundation Water Quality Index (NSF-WQI) method based on eight parameters: temperature, TDS, pH, DO, BOD, nitrate, phosphate and fecal coliform. The results of the analysis indicate that the surface water quality status falls into the "medium" category, with index values ranging from 51 to 70. Most parameters meet the Class II quality standards set by Government Regulation No. 22 of 2021, but elevated phosphate levels indicate the potential for eutrophication caused by agricultural activities. To maintain water quality, regular monitoring, public awareness campaigns and effective management are essential to support the sustainability of water resources in this region.